E-S-Quality, Perceived Value and Loyalty Intentions Relationships in Internet Retailers - Zehir, Cemal; Sehitoglu, Yasin; Narcikara, Elif; Zehir, Songul (Elsevier Science Bv, 2014)
E-commerce has become an important phenomenon in today's business life owing to developments in technology and growing internet retailing. More and more people started to prefer internet retailers while shopping and this resulted in giving more emphasis on service quality, customer perceptions and customer loyalty to those online retailers. Consequently, service quality and the factors effecting customer preferences regarding online retailers became a popular field of study. This paper examines the above-mentioned topic in Turkish business context. Our survey applied to 645 respondents using the 10 most prominent internet retailers in Turkey, with the aim of understanding associations between E-Service Quality, Perceived Value and Loyalty Intentions. According to the results of our study, we can infer that there is a strong relationship between E-service Quality and Loyalty Intentions and Perceived Value act as a mediator between them. (C) 2014 The Authors. Published by Elsevier Ltd.
10th International Strategic Management Conference -- JUN 19-21, 2014 -- Rome, ITALY
Keywords: E-service quality; perceived value; loyalty intention